Genetics and molecular biology : with fundamentals of biostatistics - Hyde, David R (Tata McGraw Hill, 2010)
Hyde’s Genetics and Molecular Biology teaches the principles of genetics with an innovative approach that emphasizes the basic concepts involved in solving problems as well as teaching students how to manipulate genetic data. This text maintains the rigor that faculty require in a genetics book, while incorporating a student-friendly presentation style that helps the reader grasp the subject in easiest manner.